The Impression of Sustainable Fashion in Customers’ Mind - A, Aarya (Journal of Global Economy, Business and Finance, 2024)
The research dives into customer perceptions of sustainable fashion and how it is impacting their decision to possibly make a purchase. With the currently evolving trends and increasing consciousness about our environment, people have started opting into more eco - friendly options in their daily life choices. Some of the options are clear but some need to be given more awareness to be implemented. Fashion has been something of that sort where people do not really look into much eco - friendly options and is ready for go for anything that gets them their “look” which delves into confidence and status that are some of the many things fashion provides them. The study has been an intersection of fashion and sustainability. The literature review shows the importance to eco - friendly materials embedded into fashion, technological innovations into the industry and a little about fair working conditions. The methodology involved a Likert Scale questionnaire consisting of 150 respondents who used different fashion brands. Results showed us a neutral overall sentiment level which signals an opportunity for marketers to explore better and create more awareness to drive customers into a purchase. Social media was a crucial response we received in terms of respondents agreeing how online media has helped them in creating more awareness about the sustainability in the fashion industry. This also gave a signal to marketers on more efficient communication strategies and how long term continuous improvements are necessary for a long term impact. They can get the most out of these findings to engage with the customers probably online and to shape an efficient sustainable fashion industry.